Microstructure and mechanical properties of a novel PM Ti–2Al–1.3V alloy in different heat treatment conditions. Issue 1 (31st December 2022) - Zhang, Yanhu; Wu, Xiaogang; Zhang, Bowen; Zhang, Youyun; Zhang, Deliang
ABSTRACT: A novel Ti–2Al–1.3V (wt.%) alloy was prepared by thermomechanical consolidation of a composite powder produced by high-energy ball milling of a mixture of TiH2 granules with a low oxygen content (0.1wt.%) and Ti–6Al–4V machining chips with a high oxygen content (0.8wt.%) at a mass ratio of 2:1. The microstructures and mechanical properties of the alloy in as-extruded state and after different heat treatments were investigated. The as-extruded alloy exhibits a martensite microstructure consisting of ultrafine and nanometer sized α' laths and aciculae and domains of layered structure containing δ(TiH) layers. The alloy in this state is brittle and fractures prematurely before yielding due to the ultrafine martensitic microstructure and hydrogen embrittlement associated with the high hydrogen content of the alloy. After vacuum annealing at 700°C for 6 h followed by furnace cooling, the alloy is further dehydrogenated with the hydrogen content being reduced to 0.008wt.%, the microstructure of the alloy changes into a full α/β lamellar microstructure with the continuous and discontinuous β layers being only 80–90 nm thick and the lamellar colony sizes being 10–30μm. The fine structured alloy in this heat treatment condition shows an excellent combination of high tensile yield strength of 996 MPa and ductility of 13.9%. After a further heat treatment of 980°C for 1 h followed by air cooling, the microstructure of the alloy consists of equiaxed α grains and α/βt lamellar structured domains ( βt = β transformed structure), and unfortunately, this microstructure leads to a significant decrease of both the tensile yield strength (to 876 MPa) and the tensile ductility (to 7.4%). The fracture behavior of the alloy in different states is also studied, and the correlation between the microstructure and mechanical properties is discussed.